Inventing criminology: essays on the rise of homo criminalis - Beirne, Piers (SUNY series in deviance and social control, 1993)
Ch. 1. Introduction -- Ch. 2. Toward a Science of Homo Criminalis: Cesare Beccaria's Dei Delitti e Delle Pene (1764). Images of Dei Delitt e Delle Pene. Reading Dei Delitti e Delle Pene as a Text of Enlightenment. Enlightenment and Darkness. The "Science of Man" in Dei Delitti e Delle Pene. From the "Science of Man" to Homo Criminalis -- Ch. 3. The Rise of Positivist Criminology: Adolphe Quetelet's "Social Mechanics of Crime" The Failure of the Classical Project. The Statistical Movement and the Compte General. Quetelet's Social Mechanics of Crime. Quetelet and His Critics -- Ch. 4. The Social Cartography of Crime: A.M. Guerry's Statistique Morale (1833). The Movement in Cartography. Crime, Development, and Education in Statistique Morale. Crime and Education: Statistique Morale and British Empirical Research -- Ch. 5. Between God and Statistics: Gabriel Tarde and Neoclassical Criminology. Classical Penality and the Positivist Revolution. The Critique of Lombroso's "Criminal Man" From Moral Statistics to a Social Psychology of Crime. The "Normality" of Crime: Tarde's Debate with Durkheim. Crime and Penality: The Neoclassical Compromise. Conclusion -- Ch. 6. Science, Statistics, and Eugenics in Charles Goring's The English Convict (1913). Calculations of Criminality: The Lombrosian Challenge. The English Convict 1: Confronting Lombrosianism. The English Convict 2: Mental Hereditarianism and Eugenics. A Reconsideration of The English Convict. Ch. 7. Epilogue -- Appendix: The Invention of the Term Criminology.